Incidence of Neuroimaging Abnormality in Children Presenting with New Onset Afebrile Seizures - R Rama Krishna Paramahamsa; Gangina Sriram (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Seizures & epilepsy affects infants & children more than any other group. There is lack of data that has looked at Neuroimaging in all children after a first afebrile, hence the present study was planned to determine incidence of Neuroimaging abnormality in children presenting with new onset afebrile seizures.Subjects and Methods: Children in the age group of six months to sixteen years who presented to the department of Paediatrics, GSL Hospital with the symptoms of first episode of afebrile seizures were evaluated prospectively. Cases with first episode of afebrile seizures that came to pediatrics department during the period of September 2012 to July 2014 were taken. Detailed history was taken and seizures categorized according to the Classification proposed by International League Against Epilepsy (ILAE) 2006.Results: Abnormal neuroimaging is seen 60 cases (75%)in which highest number of abnormal Neuroimaging is seen in 5-9 years(41.7%) followed by 30% in 9-13 years. Complex partial seizures are more common (41.3%) followed by generalized seizures (31.3%) in our study group. Brief seizures (<5mins) are more common which are 85% than prolonged seizures(>15mins) that are of 15%. Maximum affected age group in our study was age group between 5 -9 yrs 38.8% followed by 9-13 yrs 26.6%.Conclusion: Although cysticercosis incidence is greater in pork eaters, feco-oral route is also a major route of disease transmission and may also occur in population not eating pork. Cysticercosis is also more common in low socioeconomic status, poor hygiene and sanitation conditions which are evident in this study.